2009
DOI: 10.1021/la903287f
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescent Honeycomb Films Templated by Microwater Droplets

Abstract: The europium polyoxometalate anion, [EuW(10)O(36)](9-), can be transferred from an aqueous phase into a chloroform phase through encapsulation by dioctadecyldimethylammonium (DODMA(+)). The formed (DODMA)(9)[EuW(10)O(36)] complexes can self-assemble into ordered, uniform porous honeycomb films by using a simple solvent-evaporation method at the air/water interface without any extra moist airflow. TEM, SEM, and AFM observations show porous morphologies with pores having a diameter of about 2 microm and a wall d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Moreover, a heat treatment at 110°C provided C 9 H 19 COOH/Co particles with magnetic properties, and an external magnetic field was able to influence the formation of the C 9 H 19 COOH/Co-based BFA film. 355 In other reports, Wu 153,356 and Hao 357,358 demonstrated that a POM/ surfactant complex produced in chloroform could form regular BFA films by a dynamic BF process or at the air/water interface. Saito et al prepared BFA films using Al 2 O 3 NPs stabilized with a polymer containing catechol groups.…”
Section: Nonpolymeric Materialsmentioning
confidence: 94%
“…Moreover, a heat treatment at 110°C provided C 9 H 19 COOH/Co particles with magnetic properties, and an external magnetic field was able to influence the formation of the C 9 H 19 COOH/Co-based BFA film. 355 In other reports, Wu 153,356 and Hao 357,358 demonstrated that a POM/ surfactant complex produced in chloroform could form regular BFA films by a dynamic BF process or at the air/water interface. Saito et al prepared BFA films using Al 2 O 3 NPs stabilized with a polymer containing catechol groups.…”
Section: Nonpolymeric Materialsmentioning
confidence: 94%
“…In addition, Wu et al . [40,113,114,115,116,117,118] have shown that surfactant-encapsulated polyoxometalate (POM) clusters are a new type of building block for fabrication of honeycomb structures. A series of hydrophobic surfactant-encapsulated clusters prepared from POM with different compositions, shapes, and sizes, are able to self-assemble into ordered honeycomb structures [113,117].…”
Section: Formation Of Metal and Metal Oxide Nanoparticle Honeycombmentioning
confidence: 99%
“…Figure 1 shows the TEM images of an inhomogeneous microporous film (a), highly ordered honeycomb films (b,c), broken net structure (f), and HRTEM images of the highly ordered honeycombs (d, e). Also, Hao et al made photoluminescent uniform porous honeycomb films based on (DODMA) 9 [EuW 10 O 36 ] that were constructed at the air/water interface using microwater droplets as a template without any extra moist airflow [18]. The formation mechanism of the honeycomb-patterned films at the air/water interface was concluded that the condensed micrometer water droplets with hexagonal array by the quick evaporation of solvents were considered as templates for the formation of ordered microporous films [18,19].…”
Section: Polyoxometalate-based Composite Filmsmentioning
confidence: 99%